Perineal sepsis and successful surgical treatment in supralevator and ischiorectal fossa abscess: a case report. Issue 6 (16th June 2022) - Charalampopoulos, Anestis; Bagias, George; Perdicaris, Marcos; Latsonas, Panagiotis; Papagrigoriadis, Savvas; Papaconstantinou, Dimitrios
Abstract: A male 61-year-old patient presented to the emergency department with fever, leukocytosis and perineal pain. Macroscopic examination of anogluteal region demonstrated a bulky inflamed mass in the left ischiorectal fossa with a skin defect draining large amounts of pus. The suprapubic area was observed to be erythematous, with local tenderness and a palpable inflammatory mass under the skin. Computed tomography and magnetic resonance imaging revealed an abscess of the ischiorectal fossa and concomitant supralevator abscess. Examination under anesthesia revealed an internal fistula at the posterior dentate line, with pus emanating from the orifice. A bulging mass was found, protruding in the left lateral and inferior area of the rectal ampulla, a finding compatible with the supralevator abscess identified by imaging. Drainage of the abscess into ischiorectal fossa, supralevator space and suprapubic area was successful with a prompt improvement in the clinical and laboratory profile of the patient.